2019
DOI: 10.1016/j.brs.2019.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory mechanisms underlying high-frequency transcranial random noise stimulation (hf-tRNS): A combined stochastic resonance and equivalent noise approach

Abstract: 27Background: High-frequency transcranial random noise stimulation (hf-tRNS) is a 28 neuromodulatory technique consisting of the application of alternating current at random intensities 29 and frequencies. hf-tRNS induces random neural activity in the system that may boost the 30 sensitivity of neurons to weak inputs. Stochastic resonance is a nonlinear phenomenon whereby the 31 addition of an optimal amount of noise results in performance enhancement, whereas further noise 32 increments impair signal detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 60 publications
(3 reference statements)
2
87
0
Order By: Relevance
“…While our study provided proof-of-principle evidence of noise benefits at the neural population level in human cortex, we did not demonstrate the inverted U-shape function for higher tRNS intensities ( Figure 5) and can draw no inference about how much noise would be optimal for increasing the responsiveness of M1. Why did our neurophysiological study not reveal the expected inverted U-shape function for different tRNS intensities, although previous research has demonstrated this relationship when tRNS was applied while executing sensory detection tasks (Groen and Wenderoth 2016;van der Groen et al 2018;Pavan et al 2019)?…”
Section: Acute Trns-induced Noise Benefits Are Partly Consistent Withmentioning
confidence: 60%
See 2 more Smart Citations
“…While our study provided proof-of-principle evidence of noise benefits at the neural population level in human cortex, we did not demonstrate the inverted U-shape function for higher tRNS intensities ( Figure 5) and can draw no inference about how much noise would be optimal for increasing the responsiveness of M1. Why did our neurophysiological study not reveal the expected inverted U-shape function for different tRNS intensities, although previous research has demonstrated this relationship when tRNS was applied while executing sensory detection tasks (Groen and Wenderoth 2016;van der Groen et al 2018;Pavan et al 2019)?…”
Section: Acute Trns-induced Noise Benefits Are Partly Consistent Withmentioning
confidence: 60%
“…For example, the detection of low-contrast visual stimuli was significantly enhanced when the stimuli were superimposed with visual noise (Simonotto et al 1997). Recently, a similar enhancement of visual perception has been reported when noise was directly added to visual cortex via tRNS, which improved the detection of low contrast visual stimuli (van der Groen and Wenderoth 2016), visual decision making (Ghin et al 2018;Pavan et al 2019;van der Groen et al 2019), binocular rivalry (van der Groen et al 2018), and visual training in healthy participants (Fertonani et al 2011;Pirulli et al 2013) and patients (Moret et al 2018;Herpich et al 2019).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…One possible explanation for the waning of within-session tRNS effects and the absence of a cumulative effect on contrast sensitivity relates to stimulation intensity. The relationship between tRNS intensity and visual function improvement during stimulation is an "inverted U", whereby stimulation that is weaker or stronger than an optimum level has limited effects [51,52]. Lasting changes in cortical excitability induced by prior sessions of tRNS might shift the optimal stimulation intensity towards lower levels, causing a waning of tRNS effects across sessions if stimulation intensity remains constant.…”
Section: Successive and Cumulative Trns Effects On Contrast Sensitivitymentioning
confidence: 99%
“…tRNS has also been reported to enhance visual perceptual learning in adults with cortical blindness [49]. Potential mechanisms for these effects include an acute enhancement of the signal-to-noise ratio within the visual cortex due to stochastic resonance [50][51][52] and longer-lasting alterations in neural membrane function due to repetitive opening and closing of sodium channels [53].…”
Section: Introductionmentioning
confidence: 99%